THE TYPOLOGY OF PUBLIC OPEN SPACE IN PERI-URBAN UNPLANNED SETTLEMENT. CASE STUDY: KAMPONG OF KALIPATEN, TANGERANG, INDONESIA - Mohammad Ischak; Sri Novianthi Pratiwi; Maria Immaculata Ririk Winandari; Punto Wijayanto; Deasy Olivia (Universitas Trisakti, 2023)
The growth of the Tangerang area reflects the urban growth trend which leads to a wider growth pattern to the area around the Major City. One indication of the growth is the character changed of settlements that previously had a rural character into urban character, especially in building density. The growth in the number of houses as residences has resulted in changes in the type of open space and its use. Aim: This research aims to identify the type and character of open spaces in unplanned settlements that are growth very quickly because of the area directly adjacent to the Gading Serpong new town. Methodology and Results: The method used is descriptive qualitative. The type of open space is measured by the criteria of location, form, function, and land status. The character of open space is studied by connecting the existence of open space with the social interaction of the residents of the settlement. Conclusion, significance, and impact of study: The findings that have been obtained from this research are that open spaces have five types with a very prominent spatial character, namely open spaces that arise through natural social processes, are not specially designed and have a very important role in bonding the social interaction of their inhabitants.